Selenium-Dependent Regulation of Oxidative Stress and Immunity in Periparturient Dairy Cattle - Lorraine M. Sordillo (Veterinary Medicine International)
Uncontrolled or impaired immune and inflammatory responses in periparturient dairy cows are associated with increased incidence and severity of infectious diseases. The progressive development of oxidative stress during the transition from late gestation to peak lactation is thought to be a significant underlying factor leading to dysfunctional immune cell responses. Certain trace minerals, such as selenium (Se), can ameliorate oxidative stress and reduce the severity of several economically important diseases in dairy cattle including mastitis and metritis. Many of the health benefits of Se can be attributed to the antioxidant functions of selenoproteins. Changes in selenoprotein activity as a consequence of Se nutritional status can directly alter a number of critical cellular functions involved in the inflammatory response. A better understanding of how Se can optimize immune cell responses may facilitate the design of nutritional regimes that will reduce health disorders during the periparturient period.